Kinetics and Mechanism of Oxidation of Phenylalanine by Mn(III) in Sulfuric Acid Medium - Kataria, A.K.; Hiran, B.L. (Asian Journal of Chemistry, 2010)
Phenylalanine is oxidized by Mn(III) in sulfuric acid-water medium. Effect of rate by potassium permangnate, MnSO4, H2SO4, HCIO4, ionic strength, sodium pyrophosphate and temperature has been studied. Energy of activation is 91.54 kjoule mole-1. Oxidation is affected by both Mn(III) and Mn(IV). Kinetically Mn(OH)2+ and HMnO43- are the active oxidising species. A free radical mechanism is suggested.